Influence of vinification in carving on the physicochemical and phenolic composition of red wine from tropical region (Research, Society and Development, 2021)
Tropical viticulture has expanded in recent years, thanks to cultivars adaptable to the climate, enabling the Submiddle region of the São Francisco Valley to be the second largest producer of fine wines in Brazil, with emphasis on cultivating Syrah, with good adaptability and high vigor and productivity. An alternative way to prepare wines is to use amphorae, porous ceramic receptors coated with different materials, enabling the obtainment of differentiated wines due to contact during fermentation. The present work aims to evaluate the use of glass demijohns and clay pots in the physical-chemical and phenolic composition of red Syrah wines produced in the Submédio region of Vale do São Francisco. Two treatments were tested, one vinification in glass demijohns and the other vinification in clay pots. The parameters were: pH, total and volatile acidity, reducing sugars, alcohol content, total polyphenol index (TPI), color intensity, hue, previous phenolic compounds and total monomeric anthocyanins. The results inherent that there was no limited variation between the treatments studied with respect to physicochemical and colorimetric parameters, the results being within what is established in the legislation. The differences found between accumulated phenolic compounds and total monomeric anthocyanins do not negatively influence negatively in the wine quality standards.